PENGARUH FRAKSI VOLUME FIBER SISAL (Agave sisalana) TERHADAP KEKUATAN FLEKSURAL RESIN KOMPOSIT - Eko Hadianto, Liftia Layyinatus Syifa, Helmi Fathurrahman Hanafie (Universitas Islam Sultan Agung, 2018)
Background: Composite resin is filling material that used in dentistry field because of good aesthetic. Use of fiber as reinforced composite resin (FRC) begins to be developed because it has a lot of functions, such as increase strength, stiffness, material hardness from fracture, and decrease shrinkage. Fiber composite resin has syntetic characteristic and needs chemical process also has an expensive price. Therefore, natural fiber is easier to find, cheaper and can be developed as an alternative substitute of syntetic fiber. One of the natural alternative is sisal fiber. This study aims to know the effect of volume fraction of sisal fiber to composite resin flexural strength with sisal fiber concentration 1%, 2%, 3%, 4%. Method: This study was true experimental with post test only control group design which divided into 4 groups RK+FS 1% (K1), RK+FS 2% (K2), RK+FS 3% (K3), RK+FS 4% (K4). The data was analized using one way ANOVA assay and Post Hoc with significant degree 5%. Results: Mean of flexural strength sum K1=50,87 MPa, K2=42,96 MPa, K3=33,94 MPa, K4=24,32 MPa. Result of one way ANOVA assay showed value p=0,000. Result of further assay Post Hoc showed K1 with K2 p=0,002, K1 with K3 p=0,000, K1 with K4 p=0,000, K2 with K3 p=0,001, K2 with K4 p=0,000, K3 with K4 p=0,000. Conclusions: Concluded that there is good effect of sisal fiber volume fraction to composite resin flexural strength. Flexural strength RK+FS 1% has higher strength than RK+FS 2%,3%,4%. Sisal fiber could become a natural fiber alternative in dentistry restoration material.